On the derivation of estimators of Foster-Greer-Thorbecke (FGT) poverty indices - Oyedeji I. Osowole; Adebayo T. Bamiduro (CBN Journal of Applied Statistics, 2013)
Poverty analysis has relied heavily on data in summarized form and this has created dearth of knowledge on the statistical properties of Foster-Greer-Thorbecke (FGT) poverty indices. This study derived estimators of FGT poverty indices from first principles in an attempt to provide an insight into some intrinsic characteristics of FGT indices. The estimators are found to be reasonably unbiased and consistent. The estimates of the indices obtained from the estimators are approximately 53%, 22% and 12% for the head count, poverty gap and square poverty gap indices. From the conventional method, the estimates are approximately 52%, 21% and 11% respectively. The results therefore establish the validity of the derived estimators as adequate alternative measures of the three basic poverty dimensions of proportion, depth and severity.
Keywords: C13; O2; 330; FGT poverty indices; First principles; Intrinsic characteristics; Poverty dimensions; Fundamental freedoms of action and choice